PENGARUH UKURAN PERUSAHAAN, LEVERAGE DAN LIQUIDITAS TERHADAP PROFITABILITAS DI PERUSAHAAN ESPERANCA TIMOR-OAN (ETO) DILI TIMOR-LESTE - Maria, Madalena; Wiagustini, L.P.; Sedana, I.B.Panji (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.01.TAHUN 2019DO - 10.24843/EEB.2019.v08.i01.p02, 2018)
Financial performance is an analysis done to see the extent to which the company Esperanca Timor-oan has implemented by using the rules of financial performance is good and right. This study aim to determine the effect of firm size (Total asset), leverage (DER) and liquidity (QR) to profitability (ROA) in the company Esperanca Timor-Oan Unipessoal.Lda Dili East Timor. This research was conducted in the company ETO. Secondary date in this research report 2010-2012 financial year, . Testing the research hypotheses using multiple regression linear  analysis techniques, with tools Statistical Package for the Application of the Social Sciences (SPSS) 21.0 Version.The results showed that: 1).the size of the company’s significant negative effect on profitability, leverage significant positive effect on profitability, liquidity significant negative effect on profitability.